DEVELOPMENT OF PET CHEWS UTILIZING PIG EAR LOBES BY SUN DRYING METHOD - munagala, yaswanth reddy; Sudheer, K.; Reddy, G. V. Bhaskar; Venkateswarlu, S.; Naveen , Z. (Journal of Meat Science, 2023)
The slaughter of pig is mainly done for its meat and offal’s, along with there is generation of other by-products like ears, feet, lard, blood, bones etc. The present work was designed in order to utilize the pig ear lobes as dried pet chews by using sun drying method which serves as feed stuff for pet animals. In sun drying method the results revealed significant (P
Keywords: Million; Enterprise; Moisture; Significant; Treatments